(untitled) (Research, Society and Development, 2021)
High blood glucose levels results in deleterious effects to the the peripheral nervous system, causing sensory and motor damage. Neuromotor reaction time (RT) measurements are a sensitive indicator of functional impairment in different populations. The aim of the present study was to identify and analyze national and international literature on the impact of diabetes mellitus 2 (DM2) over RT measurements and the main mechanisms for such correlation. This integrative review was conducted by ressarching the LILACS, BIREME, SCOPUS, Cochrane and Pubmed databases in July 2020 and August 2020. In the end, 14 articles were selected, all in English. The results show that the TR in DM2 cases associated with neuropathy was higher than expected when compared to other populations. Therefore, the RT measurement is a viable alternative in the diagnosis of DM2-associated neurological disorders, due do its sensitivity to changes in the velocity of nerve impulse conduction, slowed down in DM-2 associated neuropathy. RT assessments can be employed as diagnostic and screening measures when dealing with these patients, with emphasis on preventing severe outcomes such as ulcers and amputations. Future studies should investigate possible instrumental and methodological standardization, in addition to the validation of a national product that explores RT in the Brazilian population.